Manuel Murguía and Rosalía de Castro in her Early Stages as Narcisa Pérez Reoyo’s Work - López, Teresa (Madrygal. Revista de Estudios Gallegos, 2015)
In 1865, Narcisa Pérez Reoyo published in A Coruña Cantos de la infancia, her first collection of poems, prefaced by Manuel Murguía. It includes a poem dedicated to Rosalía de Castro. This article addresses the relationship between the Murguía-Castro couple and the young writer, in the context of 19th-century literature written by women and of the development of Galician literature.